PENYULUHAN PERAWATAN WAJAH SECARA TRADISIONAL DI DASAWISMA CEMPAKA 15 WARUNGBOTO YOGYAKARTA - Wahyu Tusi Wardani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Since millennia, the phenomenon of beauty as a part of a woman's lifestyle has been felt. Throughout the history of mankind, body care procedures have been recognized as cultural aspects (Kustanti, 2009). Some women have begun to contemplate how to beautify themselves in the traditional style, owing to the high rate of failure in current therapies and the fact that it was regarded inexpensive (Indarto 2015). As a result, the instructor is considering performing community service in the area of traditional facial care advice. The goal of this traditional face care counseling is to improve moms' knowledge of safe traditional facial treatments. Members of Dasawisma Cempaka 15, RT 30, RW 07 Warungboto, Umbulharjo, Yogyakarta took part in the counseling. On Wednesday, October 7, 2020, at 16.00-17.00 WIB, this activity will be held at the nearby Dasawisma RT Hall. There were various stages to this coaching. It began with a survey, approval, paper preparation, and distribution of pre-tests to residents' homes. Counseling and discussion took place on the counseling day. The activity came to a close with the distribution of the post-test and evaluation materials. This counseling session had a total of 20 participants. According to the data, 80% of the participants said they had never attended a standard facial care counseling session. All of the individuals had issues with their skin. Black spots (11) are the most common issue, followed by acne problems (9). According to the results of the post-test, 85 percent of the participants had used natural components as face health treatments. The conclusion of this counseling is that participants' understanding of traditional face treatments can be improved by facial care counseling. People can correctly administer traditional facial treatments after completing this health education.